Social Entrepreneurship Education: Policy, Core Themes and Developmental Competencies - Chell, Elizabeth; Karataş-Özkan, Mine; Nicolopoulou, Katerina (Senate Hall, 2007)
Examining the policy context for social enterprises in the UK, in this paper, we argue for a comprehensive educational approach to meet the needs of social entrepreneurs and other stakeholders associated with social enterprises. We separate out the requirement of business competence and entrepreneurial capability that will enable the social entrepreneur and his team to assure the sustainability of the enterprise. We propose a framework that incorporates - from an education perspective- a number of specific areas in terms of skills and competences that social enterprises and social entrepreneurs should develop in order to tackle the challenges and needs in the domain of their business activity. We highlight that there are specific competencies to be developed in order for social entrepreneurship to be a terrain of more sustainable, innovative and creative venturing. The research discusses the value of developing a layered understanding of an educational approach for social entrepreneurship, whereby the scales of micro/meso/macro are taken into consideration: the individual experience, the relational community experience and the macro level experience with the field of entrepreneurship.
Keywords: social enterprise|social entrepreneurship|education|not-for-profit|sustainability|skills.